Determinants and Measurements of Sustainability Reporting Quality: A Systematic Literature Review - Yusli Mariadi; Ni Luh Putu Wiagustini; Ni Ketut Rasmini; I Gusti Ayu Nyoman Budiasih (Jurnal Ilmiah Akuntansi, 2025)
Sustainability Reporting Quality (SRQ) has emerged as a critical aspect of corporate accountability in the context of the worldwide implementation of sustainability disclosure standards, including the Global Reporting Initiative (GRI), ISSB, and IFRS Sustainability Disclosure Standards. This study does a systematic literature review (SLR) of 33 empirical publications published from 2013 to 2023 to consolidate knowledge regarding the factors and assessment methodologies of SRQ. The research finds four main factors that affect the situation: corporate governance, stakeholder involvement, board diversity, and demands from outside institutions. Governance procedures and stakeholder participation typically improve SRQ, although data on board diversity is still uneven and sometimes shows only symbolic compliance. External factors, like rules set by the government, industry standards, and best practices for assurance, also affect the quality of disclosures, especially in diverse institutional settings. The review shows that SRQ assessment methods are very different from each other. Some use GRI-based content analysis and score indices, while others use qualitative evaluations. This makes it hard to compare and validate studies. To tackle this fragmentation, the article proposes the creation of a unified and validated SRQ measurement system that integrates contemporary global sustainability criteria. This work enhances theory and practice by elucidating the multidimensional structure of SRQ, pinpointing methodological deficiencies, and offering guidance for future research centered on digital reporting, stakeholder trust, and regulatory harmonization.